Declaration Of Understanding Radicalism To Islam (Critical Analysis of Islamic Religious Educational Materials in Response to Allegations of Understanding Radicalism to Muslims) - Lalu Gede Muhammad Zainuddin Atsani; Ulyan Nasri (Kamaya: Jurnal Ilmu Agama, 2021)
The purpose of this study is to critically analyze or re-measure Islamic religious education materials in countering accusations of radicalism to Muslims. The term radicalism has become a familiar term attached to a group in Islam. Indicators to call groups in Islam radicalism to include terrorism, anarchists, rebels, and extremists. The research method uses a descriptive type of research. The results of this study are one of the causes of the trapping of elements in radicalism, namely a partial understanding of religion and tends to the nature of fanaticism. This trait then results in a sense of superiority over followers of other religions. Failing to understand the concept of jihad in religion makes someone take a shortcut by spreading terror to innocent people. the logical consequence of this interpretation is the juxtaposition of terrorism as the fruit of radicalism. This hypothesis is reasonable, considering that various terrorist activities in various parts of the world always act in the name of jihad carried out by Muslims as a form of obedience to God. This has led to various upheavals which, without realizing it, will not only have implications for the decline in national stability. However, it even sparked a negative response from various parts of the world. Therefore, it is necessary to have an inclusive understanding of religion so that religious adherents realize that plurality is a necessity. Seeing these problems, there needs to be a strengthening and reaffirmation of the originality of Islamic teachings that contain humanist pluralistic and tolerant values. The conclusion is that a very strategic role, in this case, is that Islamic religious education materials must be able to reconstruct relevant materials to counteract accusations of radicalism. It is at this point that the focus of the study in this article is trying to critically analyze or re-measure Islamic religious education materials that tend to be humanist-pluralist and tolerant to ward off accusations of radicalism in Islam.